Kebijakan Pengupahan di Indonesia - Rochadi, Sigit (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1996)
The issue of wages is by all standards. the most crucial in albor relationship, so that in order to protect and improve on the prosperity of workers, government can not surrender its responsibility over wages to the forces of market mechanism. Besides, it is absolutely desirable that government issues a policy on minimum wage rates/6r workers. FroÃÂ»: the results of the anahsis of this work. we can never thelecs, draw a conclusion shot the wage policy which is pursued by governmewni it no! effective, .cc that it is not able to achieve the objecti:v that government intended a far. The failare of th,s wage policy can be attributed so four *tors; (1) the level of policy formulation. (2) the survey or the revision of this minimum wages which is not done perediocally. (3) legislation on wages and (4) lack of instruments which can ej: fectively forces the employers to observe legislation on wages. As a solution, the author suggests the necessity to strengthen the negotiating position of the workers to encompass their wider acces to government policy.